Jewellery box / Wan Nur Athirah Wan Zaidi - Wan Zaidi, Wan Nur Athirah (2022)
The National Library of Malaysia (or PNM) is the agency responsible for keeping the collection of (مليسيا) knowledge treasures at the national level for present and future generations. The motif, shape, from an artistic line on Tuaran mosque Sabah were transformed into jewelry box design though ideation and development of idea.